Analisis Pengaruh Disiplin Kerja, Budaya Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Angkasa Pura Suport - Rama Edri Hanafi; Asrul; Rakhmat (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
K Employees are the company's main asset and have a strategic role in the organization, namely as thinkers, planners, implementers and controllers of organizational activities. The purpose of this study is to obtain a clearer picture of the influence of work discipline, work culture, work environment on employee performance at PT Angkasa Pura Suport.The method used in this research is observation, namely conducting direct research on PT Angkasa Pura Suport and conducting interviews with the company, as well as using a questionnaire (questionnaire) to respondents who are customers of PT Angkasa Pura Suport. Analysis of the research data was carried out using quantitative analysis methods. In analyzing the relationship between the influence of work discipline, work culture, work environment on employee performance by knowing the strength or weakness of the relationship between the independent factor X (Work Discipline, Work Culture, Work Environment) to the dependent factor Y (Employee Performance), then linear regression analysis is used double. This study also uses analysis of the coefficient of determination (R²), t test (partial) and F test (simultaneous). Based on the calculation of multiple linear regression analysis, the results obtained are Y = -1.624+ 0.295 X? + 0.373 X? + 0.343 X3. From the results of calculating the coefficient of multiple linear regression analysis, it can be seen that it has a positive relationship, meaning that work discipline, work culture, work environment applied to PT Angkasa Pura Suport can affect employee performance. From the results of the calculation of the coefficient of determination analysis shows that work discipline, work culture, work environment have an influence on employee performance of 87.70% and the rest is influenced by other factors. The results of the t-test hypothesis test both work discipline, work culture, work environment, on employee performance both have values: t count > t table, namely the value of work discipline with a result of 4.876 > 1.987, work culture value with a result of 5.513 > 1.987, the value of the work environment with a result of 6.722 > 1.987 and an employee performance value with a result of 4.430 > 1.987. Based on the calculation results of the F test (simultaneous) it is found that the calculated F value is greater than F table (203.781 > 24.77), so it is concluded that there is a significant influence between work discipline, work culture, work environment on employee performance at PT Angkasa Pura Suport.